RESOLUSI KONFLIK KEPENTINGAN: PENERAPAN PEACE CULTURE DALAM KONFLIK ANTAR KELOMPOK KEAGAMAAN DI KOTA BITUNG - Andreas Bryian Gultom (Institut Agama Kristen Negeri Toraja, 2026)
Abstract: This research aims to analyze the causes of conflicts that occur in Bitung to produce conflict resolutions based on the culture of the people in the area. Bitung is actually a city with the highest religious tolerance in North Sulawesi, but conflicts will continue to occur in the area at 2023 involving the Barisan Solidaritas Muslim (BSM) group as supporters of Palestine and the Manguni Christian group and the Makatana institution as supporters of Israel. Conflict management that does not understand the causes of conflicts that can be complex becomes a problem in conflicts in Bitung. The qualitative approach is used with a literature study method that focuses on conflict of interest theory by Dahrendorf and peace culture theory by Galtung as a primary source and previous research reports that focus on journals and news related to the conflict in Bitung as secondary sources analyzed through documentation techniques. The results of this study show that the cause of conflict is not only caused by theological factors, but also differences in support interests related to the interests of each group which are influenced by several fundamental factors and the uneven distribution of authority between the superordinate group and the subordinate group. Abstrak: Penelitian ini bertujuan menganalisis penyebab konflik yang terjadi di Bitung untuk menghasilkan resolusi konflik berdasarkan kebudayaan masyarakat di daerah tersebut. Bitung sebenarnya kota yang rukun dengan toleransi beragama tertinggi di Sulawesi Utara, namun konflik tetap terjadi di daerah tersebut pada tahun 2023 yang melibatkan kelompok Barisan Solidaritas Muslim (BSM) sebagai pendukung Palestina dan kelompok Kristen Manguni serta Adat Makatana sebagai pendukung Israel. Pengelolaan konflik yang belum memahami penyebab konflik yang dapat bersifat kompleks menjadi permasalahan dalam konflik di Bitung. Pendekatan kualitatif digunakan dengan metode studi pustaka yang berfokus pada teori konflik kepentingan oleh Dahrendorf serta teori peace culture oleh Galtung sebagai sumber primer dan laporan penelitian sebelumnya yang berfokus pada jurnal serta pemberitaan terkait konflik di Bitung sebagai sumber sekunder yang dianalisis melalui teknik dokumentasi. Hasil penelitian ini menunjukkan bahwa penyebab konflik tidak hanya disebabkan oleh faktor teologis, melainkan juga perbedaan kepentingan dukungan yang berkaitan dengan kepentingan masing-masing kelompok yang dipengaruhi oleh beberapa faktor fundamental dan distribusi otoritas yang tidak merata antara kelompok superordinat dan kelompok subordinat.